Surgical Treatment of Patients with Dislocation of IOL — Fibrosed Capsule Bag Complexes - D. I. Ivanov; V. N. Nikitin (Oftalʹmologiâ, 2022)
Violation of the correct location of the complex IOL capsule bag (CICB) in the delayed postoperative period occurs with a frequency of 0.2 to 2.8 %. The basis of the pathogenesis of this complication is the destruction of the zonal ligament due to progressive pseudoexfoliative syndrome, as well as the process of fibrosing the capsule bag. The stage of the flow and the different degree of severity of each mechanisms determines the variety of clinical manifestations. CICB dislocation in combination of these two mechanisms requires a special approach to treatment.Objective: to develop a system of surgical treatment of IOL dislocations in contract capsule syndrome, with varying degrees of severity, combined with the weakness of the ligament apparatus of the lens, and to present the results of its use.Patients and methods. Retrospective analysis of 55 cases of CICB dislocations with the observation period of more than 4 years operated in 2014-2016. Number of dislocations with certain IOL type: Hydrophilic monolithic — 27, Hydrophilic monolithic — 11, Hydrophilic three-part — 10, Hard — 7. The selection criterion was the presence of CICB dislocation in the combination of weakness of the ligament apparatus (II–III st. of severity) and contraction capsule syndrome, with varying degrees of severity. A system is proposed to allow a low-invasive repositioning of intraocular lenses dislocated with a fibrous capsule bag with subsequent suture fixation to the iris. Signs used for choice of surgical technique: localization of capsule bag fibrosis, contract effect of capsule bag fibrosis on IOL position and correct location of haptic elements, size, and severity of equatorial lens masses (Semmering ring). In cases when insufficiency of the ligament apparatus prevails, with insignificant fibrosis of the capsule bag, without contractional influence, fixation of KIKM to iris is carried out without cutting of the capsule bag (method 1). As the fibrous changes of the front or back leaf of the capsule progress without changing the position of IOL inside the capsule bag due to contraction, along with fixation of KIKM, the fibrous front/back capsule is excised (method 2). The variant of complete removal of the fibrous capsule bag is used in faraway stages of CCS with further fixation of IOL to the iris (method 3).Results. The data of BCVA and IOP of patients treated by a certain method (before the operation, early postoperative period (2–5 days), delayed period (more than 4 years)) are presented.Conclusion. Surgical treatment of patients with CICB dislocation combining manifestations of Capsule contraction syndrome and weakness of the lens ligament apparatus can now be standardized using a proper approach and certain methods of treatment, but requires a comprehensive assessment of such parameters as the safety of the ligament apparatus, the localization and degree of fibrous changes of the anterior / posterior capsule, the contractional effect of the capsule bag fibrosis on the front position of the IOL optics and the correct location of the haptic elements, the severity of the ring.